Student well-being: the impact of belonging, COVID-19 pandemic related student stress, loneliness, and academic anxiety - Dost, Gulsah (Frontiers in Psychology, 2025)
IntroductionThis research investigates the relationship between collegiate community and degree department belonging, loneliness, COVID-19 pandemic related student stress, coping self-efficacy, and academic anxiety among UK collegiate context. The study focuses on how these factors have shaped students’ academic and social experiences in the post-pandemic era, with particular emphasis on variations based on gender as well as home versus international status among both undergraduate and postgraduate cohorts.MethodsThis study utilized structural equation modelling (SEM). A sample of 430 students was administered, with 284 (66%) completed by female students and 120 (28%) by male students. The number of undergraduate students was (N = 244, 56.7%), and (N = 184, 42.8%) participants were postgraduate students.ResultsThe research findings indicate that stress related to COVID-19 has adversely affected both types of belongingness— collegiate community and degree department belonging —while concurrently elevating academic anxiety across diverse demographic groups. Loneliness emerged as a significant mediating variable, with pronounced effects observed among international and male students. The presence of academic anxiety exacerbated feelings of loneliness and diminished coping self-efficacy, particularly in female and undergraduate cohorts. International students experienced notable disruptions in their sense of collegiate belonging and heightened levels of loneliness. Undergraduate students demonstrated greater susceptibility to stress-induced declines in belongingness, whereas postgraduate students reported more severe ramifications of loneliness on their academic and social relationships.DiscussionThese results underscore the necessity for targeted interventions designed to foster social connectedness, alleviate academic anxiety, and bolster support systems within the post-pandemic educational framework.